1984
DOI: 10.1002/bip.360230808
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational circular dichroism of polypeptides. II. Solution amide II and deuteration results

Abstract: SynopsisVibrational CD (VCD) of amide I and I1 vibrations of several a-helical polypeptides have been measured in solution. For the amide I1 as well as the amide I [previously published: Lal, B.B. & Nafie, L.A. (1982) Biopolymers 21, 21611 we find the VCD to be characteristic of the polypeptide secondary structure. Amide I1 bands of right-handed u helices were all found to have negative VCD and to have their maximum rotational strength for the parallel (low-energy) component. However, left-handed a helices for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 30 publications
4
44
0
2
Order By: Relevance
“…FTIR are widely used to explore the secondary structure of polypeptides [21,22]. Absorption of stretching of the C@O (amide I) at ca.1655 cm À1 and the deformation and stretching of the NAH bond (amide II) at ca.1550 cm À1 indicate that an a-helix conformation is adopted by the polypeptide blocks [23].…”
Section: Conformation Of Polypeptide Blocks In Bulkmentioning
confidence: 99%
See 1 more Smart Citation
“…FTIR are widely used to explore the secondary structure of polypeptides [21,22]. Absorption of stretching of the C@O (amide I) at ca.1655 cm À1 and the deformation and stretching of the NAH bond (amide II) at ca.1550 cm À1 indicate that an a-helix conformation is adopted by the polypeptide blocks [23].…”
Section: Conformation Of Polypeptide Blocks In Bulkmentioning
confidence: 99%
“…Here, the secondary structures under this condition were estimated in detail using an internet available CD reference database ''DICHRO-WEB'' via Continll program [26,27]. It was found that the peptides adopted a complex secondary structure upon heating, which consisted of 16.3% a-helix, 22.3% b-sheet, 26.4% turns, and 35% unordered coil at 70°C, whereas they showed a well-defined conformation of 94.7% a-helix and 5.3% b-sheet at 5°C. It is known that the a-helix originates from intramolecular hydrogen bond between peptide chains.…”
Section: Conformation Of Polypeptide Blocks In Solutionmentioning
confidence: 99%
“…Deuteration has definite effects on the helix VCD, changing the amide I from a couplet to a three-feature band shape (Sen & Keiderling, 1984;Baumruk & Keiderling, 1993). It is reasonable to assume that some, perhaps smaller, changes will occur for the VCD of other secondary structure types on deuteration.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%
“…In fact, VCD has been successfully used in the past to determine secondary structural information in peptides and proteins. 17 We have made use of VCD for deducing the structure of gramicidin in different environments. 18 The solution and crystalline structures need not be the same, because packing effects in the crystalline state can influence the structure.…”
Section: Introductionmentioning
confidence: 99%